ENHANCING ENGLISH SPEAKING SKILLS FOR ELEMENTARY LEARNERS THROUGH ROLE PLAY: CHALLENGES AND OPPORTUNITIES - Monica Widjaja; Dewi Listia Apriliyanti (PROJECT (Professional Journal of English Education), 2022)
Speaking as the output of language requires the speaker to have vocabulary, pronunciation, grammar, and fluency ability. On the contrary, young learners have a tendency of short term memory. It makes the language teachers for young learner creative. Hence, this research is conducted to investigate teachers' and students’ responses to teaching English speaking skills using role-play technique, and to identify students' difficulties during the learning activities. A descriptive qualitative design has been applied in this research. The primary participants in this research were twenty-nine students of the fifth-grade elementary private school in Bandung. The instruments used were observation, questionnaire, and open-ended question. This study revealed that the students became exciting and motivating to learn English because they had chance to practice their pronunciation and fluency. Moreover, they could understand the material given easier and involve instantly into the material to integrate it with their real life. Some of students in middle-low ability still troubled in pronunciation followed by the problems in vocabularies adequate. It gives negative effect to their fluency and courage to speak English. Overall, the role play method can overcome the difficulties in speaking English. Keywords:  Vocabulary, Speaking Ability, Role Play Method